2006
DOI: 10.1111/j.1740-0929.2006.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in stearic acid proportions in adipose tissues and liver lipids in fatty liver of dairy cows

Abstract: Samples of liver and perirenal, mesenteric and subcutaneous fat were collected from 16 sick necropsied dairy cows to evaluate the fatty acid profiles in the hepatic and adipose tissues associated with advanced fatty liver or hepatic lipidosis. Hepatic triglyceride and eight fatty acids were measured in the hepatic and adipose tissues. Six cows had more than 3% triglyceride on fresh weight in their livers and were classified as having fatty liver. Stearic and linoleic acid proportions in the liver decreased mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
(19 reference statements)
6
8
1
Order By: Relevance
“…In general, the SUBC FA profile was in agreement with those reported in dairy (Rukkwamsuk et al, 2000;Sato and Inoue, 2006;Douglas et al, 2007;Zachut et al, 2010a) and in beef cattle (Eichhorn et al, 1986;Beaulieu et al, 2002;Oka et al, 2002;Siebert et al, 2003). Omental FA profiles are seldom reported in both dairy (Sato and Inoue, 2006) and beef cattle (Beaulieu et al, 2002) but seem consistent with perirenal FA profiles (dairy: Sato and Inoue, 2006;beef: Eichhorn et al, 1986;Beaulieu et al, 2002;Oka et al, 2002). In our study, the FA with the highest contribution to the ABD and SUBC FA was 18:1 cis-9, which is in agreement with previous dairy (Rukkwamsuk et al, 2000;Sato and Inoue, 2006;Douglas et al, 2007;Zachut et al, 2010a) and beef cattle studies (Eichhorn et al, 1986;Beaulieu et al, 2002;Oka et al, 2002;Siebert et al, 2003), although the concentrations mentioned in previous studies were higher (Figure 2).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the SUBC FA profile was in agreement with those reported in dairy (Rukkwamsuk et al, 2000;Sato and Inoue, 2006;Douglas et al, 2007;Zachut et al, 2010a) and in beef cattle (Eichhorn et al, 1986;Beaulieu et al, 2002;Oka et al, 2002;Siebert et al, 2003). Omental FA profiles are seldom reported in both dairy (Sato and Inoue, 2006) and beef cattle (Beaulieu et al, 2002) but seem consistent with perirenal FA profiles (dairy: Sato and Inoue, 2006;beef: Eichhorn et al, 1986;Beaulieu et al, 2002;Oka et al, 2002). In our study, the FA with the highest contribution to the ABD and SUBC FA was 18:1 cis-9, which is in agreement with previous dairy (Rukkwamsuk et al, 2000;Sato and Inoue, 2006;Douglas et al, 2007;Zachut et al, 2010a) and beef cattle studies (Eichhorn et al, 1986;Beaulieu et al, 2002;Oka et al, 2002;Siebert et al, 2003), although the concentrations mentioned in previous studies were higher (Figure 2).…”
Section: Discussionsupporting
confidence: 88%
“…As the data are limited in this research area, we compared our results for the individual FA (Figure 2) and the Δ 9 -desaturase indices (Figure 3) with data from both dairy and beef cattle. In general, the SUBC FA profile was in agreement with those reported in dairy (Rukkwamsuk et al, 2000;Sato and Inoue, 2006;Douglas et al, 2007;Zachut et al, 2010a) and in beef cattle (Eichhorn et al, 1986;Beaulieu et al, 2002;Oka et al, 2002;Siebert et al, 2003). Omental FA profiles are seldom reported in both dairy (Sato and Inoue, 2006) and beef cattle (Beaulieu et al, 2002) but seem consistent with perirenal FA profiles (dairy: Sato and Inoue, 2006;beef: Eichhorn et al, 1986;Beaulieu et al, 2002;Oka et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…The major FA in adipose tissue are C16:0, C18:0, and C18:1 [8][9][10] and are expected to be increased in plasma postpartum as cows mobilize FA from adipose tissue, as was observed with increased postpartum plasma C16:0 and C18:1 relative to prepartum plasma in both HYK and nonHYK cows in the current study. Although both groups mobilized adipose tissue, the greater BCS loss and elevated NEFA of HYK cows would suggest that FA derived from adipose Expression of PC, PC: PCK1, and PC:PCK2 were log transformed for analysis to achieve normal residuals and thus are reported using the 67% confidence interval.…”
Section: Plos Onementioning
confidence: 54%
“…Prior work has demonstrated that subcutaneous adipose tissue FA profile does not change across the transition period [ 8 ], making it unlikely that preferential mobilization plays a major role in differential FA metabolism, at least within the subcutaneous depots. Relative to C16:0 and C18:1, C18:0 is present in lower proportions in subcutaneous fat, but at a greater proportion in internal fat stores [ 9 , 10 ] which are also mobilized during the peripartum period [ 32 ]. It is unknown if the difference in FA profiles and metabolic activity between adipose tissue depots [ 33 ] may impact the circulating FA profile or preferential mobilization and metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation